2021
DOI: 10.3389/fpsyg.2021.730172
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Prints of Grit

Abstract: While scientific interest in understanding the grit trait has grown exponentially in recent years, one important gap in the grit literature relates to its biological and neural substrate. In the present study, we adopted a hypotheses-driven approach in a large sample of young adults (N = 120) with diverse educational backgrounds and work experiences in order to investigate the electrophysiological correlates of grit both during rest and while performing a learning task. Additionally, we selected a measure of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…We first performed Spearman correlations between the main variables of interest to identify potential predictors of grit. As can be seen in Table 2 , the two personality traits highly correlated with grit and its facets (please, note that the correlation between BISS and Grit has been previously informed in [ 52 ], where BISS was used as a control variable to partial out the variance explained by this variable in the relationship between grit and the reported brain measures). Correlations between grit and the facets of the FFMQ are available in Supplementary Material 3 in S1 File .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We first performed Spearman correlations between the main variables of interest to identify potential predictors of grit. As can be seen in Table 2 , the two personality traits highly correlated with grit and its facets (please, note that the correlation between BISS and Grit has been previously informed in [ 52 ], where BISS was used as a control variable to partial out the variance explained by this variable in the relationship between grit and the reported brain measures). Correlations between grit and the facets of the FFMQ are available in Supplementary Material 3 in S1 File .…”
Section: Resultsmentioning
confidence: 97%
“…One possible explanation of this discrepancy is the lack of correspondence between the self-reported measures of self-control and the executive-control indexes derived from experimental tasks [i.e., see, 68 , 69 ], as well as between brain activity and performance. Thus, for example, previous results have showed grit to be linked to electrophysiological activity thought to reflect better effortful control in a learning task, but not to better learning performance [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred twenty people (Mage = 23.11, SDage = 4.19, Range = 18-33, 69% female) completed the study in exchange for course credits (0.1credit/40 min) or monetary reward (7€/1 h). This sample took part in a larger individual differences study from which other non-overlapping findings have been already reported (Aguerre et al, 2020(Aguerre et al, , 2021(Aguerre et al, , 2022. To confirm that the sample size of the bigger project was enough to capture the desired effects, we calculated a priori power analysis (G*Power 3.1.9.2; Erdfelder et al, 1996) based on the effect of the linear regression reported by Kong et al (2016), with an R 2 = .14, as we also adopted an regression approach.…”
Section: Methods Participantsmentioning
confidence: 99%
“…We wanted to know whether it is possible to implement such a system based on brain signals recorded above the frontal and occipital cortices. The role of theta-beta ratio (TBR) (i.e., the ratio of power within the 4–7 Hz and 13–30 Hz ranges) of signals measured above the frontal areas have been reported in relation to attentional control 31 33 , emotion regulation 34 , 35 , grit (perseverance) 36 and correct time perception 37 negatively and to mind wandering positively 38 40 . Despite of not being primary sites of motor planning or execution, occipital areas have also been mentioned in the literature in the context of motor control and SMR NF.…”
Section: Introductionmentioning
confidence: 99%